THE EVOLUTION OF APPROACHES TO STRATEGIC MANAGEMENT OF THE DEVELOPMENT OF UKRAINE’S VITICULTURE AND WINEMAKING SECTOR IN THE CONTEXT OF GLOBALIZATION AND POST-WAR RECOVERY - VDOVENKO, Nataliia; LOPATYNSKYI, Yurii; SARKISIAN, Hanna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article proposes theoretical approaches to managing the development of viticulture and winemaking, which have evolved from administratively planned models to modern strategic management concepts that integrate institutional, innovative, environmental, and marketing components. It has been established that, in this context, it is important to systematize existing theoretical schools and approaches and adapt them to the specifics of the national economy and the international competitiveness of Ukrainian wine. Attention is drawn to the fact that the recovery and further development of the industry must be pursued not only in terms of restoring production but also through the implementation of strategic instruments focused on long-term competitiveness and export potential of products. In the course of analyzing the theoretical foundations of strategic management in the development of Ukraine’s viticulture and winemaking sector, four stages in the evolution of scientific perspectives have been identified: the directive (planning) stage; the market adaptation stage; the institutional-innovation stage; and the current smart and digital stage. At this contemporary stage, under the influence of globalization and the European integration vector of Ukraine’s development, domestic researchers are increasingly turning to the concepts of smart specialization, cluster approaches, digital governance, and the green economy. Relevant studies now address the impacts of climate change, demographic factors, market instability, and logistical challenges on the formation of development strategies for the viticulture and winemaking sector. There is growing interest in scenario-based management models, risk assessment systems, energy and resource monitoring tools, and analyses of global best practices for strategic partnerships between the state, business, and the scientific community. The current period is marked by active digitalization and Ukraine’s integration into pan-European strategies, including the European Green Deal, smart specialization strategies, and the development of agricultural clusters. The analytical ESM-VVK model presented in this article for managing the development of the viticulture and winemaking complex in Ukraine is based on a systemic approach to evaluating the effectiveness of strategic governance across six dimensions: institutional, technological, competitive, market, resource, and global. The model makes it possible to formalize a comprehensive set of influencing factors that determine the effectiveness of managerial decisions under global challenges.
Keywords: globalization; mechanism; strategic management; sector; viticulture and winemaking complex; regulation; competitiveness; instrument; framework; export; wine; smart specialization; SMART governance; agricultural sector; post-war recovery